Предмет: Алгебра,
автор: оченьважнолюди
(2х-3х)^2+(3х-3)(3х+3)+21х при х=-2 равно 34
Помогите
Ответы
Автор ответа:
0
(2х-3х)²+(3х-3)(3х+3)+21х=
=(-х)²+9х²-9+21х=
=8х²+21х-9
при х= -2
8(2)²+21(-2)-9=32-42-9=-19
Ответ: -19≠34
=(-х)²+9х²-9+21х=
=8х²+21х-9
при х= -2
8(2)²+21(-2)-9=32-42-9=-19
Ответ: -19≠34
Похожие вопросы
Предмет: Алгебра,
автор: 27361682
Предмет: Математика,
автор: Emaemamazvonit
Предмет: Алгебра,
автор: kruppovajuliya
Предмет: Химия,
автор: sokolekilya
Предмет: Биология,
автор: настя2563